Hydrodynamic comparison of different geometries of square cross-section airlift bioreactor using computational fluid dynamics - Esperança, Mateus N.; Cerri, Marcel O. [UNESP]; Mazziero, Vítor T. [UNESP]; Béttega, Rodrigo; Badino, Alberto C. (De Gruyter, 2023)
The hydrodynamics of airlift bioreactors, which offer an interesting alternative to conventional stirred-tank bioreactors, has generally been evaluated using experimental approaches, requiring time, energy, and reagents. However, computational fluid dynamics (CFD) has emerged as an important and valuable tool for the analysis and design of these devices, saving time and experimental effort, while providing a large amount of information. In this study, four geometries of a square cross-section 10-L split airlift bioreactor operating with distilled water were simulated using CFD, and the hydrodynamics variables gas hold-up and liquid velocity were evaluated. CFD satisfactorily predicted the hydrodynamic parameters, when compared to experimental data, allowing adequate prediction of the shear rate distribution in airlift bioreactors. The results indicated that different shear rate distributions were obtained by geometric modifications in the bioreactor, showing that its design should be considered to satisfy different specific bioprocess requirements.
Keywords: airlift bioreactor; computational fluid dynamics; gas hold-up; hydrodynamic; shear rate